2007
DOI: 10.5575/geosoc.113.171
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic boundary between the Sanbagawa belt and the Shimanto belt in central Shikoku, Japan

Abstract: Mode of occurrence of high-P/T regional metamorphic belt is a key to understand the tectonic evolution of deepseated accretionary complex along the subduction zone.Thermobaric structure of the high-pressure and/or ultrahigh-pressure metamorphic belts have been examined to clarify their exhumation process e.g. Terabayashi et al., 1996;Ota et al., 2000; Correlation with surrounding geologic units is also important to verify the exhumation tectonics, and high-P/T regional metamorphic belts are bounded by a subhor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 36 publications
(16 reference statements)
4
86
0
Order By: Relevance
“…120-110 Ma (Okamoto et al, 2004) , which occupy the uppermost portion of the Sanbagawa Belt. Although some previous studies suggested that the Sanbagawa Belt consists of metamorphosed Late Jurassic to Early Cretaceous accretionary complex, the present study shows that the belt is largely occupied by metamorphosed Late Cretaceous rocks : the Shimanto Metamorphic Rocks of Aoki et al (2007) . As a result, the Sanbagawa Belt consists of the following three units with different protolith ages : (1) Lower Unit of Shimanto Metamorphic Rocks with proto- …”
mentioning
confidence: 73%
“…120-110 Ma (Okamoto et al, 2004) , which occupy the uppermost portion of the Sanbagawa Belt. Although some previous studies suggested that the Sanbagawa Belt consists of metamorphosed Late Jurassic to Early Cretaceous accretionary complex, the present study shows that the belt is largely occupied by metamorphosed Late Cretaceous rocks : the Shimanto Metamorphic Rocks of Aoki et al (2007) . As a result, the Sanbagawa Belt consists of the following three units with different protolith ages : (1) Lower Unit of Shimanto Metamorphic Rocks with proto- …”
mentioning
confidence: 73%
“…Recently, Aoki et al (2007) found Late Cretaceous detrital zircons present only in a sample from the Oboke nappe while they found only Proterozoic zircons in a sample from the Besshi nappe. They concluded that the Oboke nappe acts as a "window" in which the tectonically lower Late Cretaceous accretionary complex, i.e., Shimanto Belt, appears.…”
Section: Relation Between the Sanbagawa Belt On Shikoku Island And Kamentioning
confidence: 99%
“…This indicates that the main provenances of clastic rocks in the Sanbagawa Belt on the Kanto Mountains are Cretaceous igneous rocks. Although Proterozoic to Jurassic detrital zircons are found in clastic rocks in Japan Tsutsumi et al, 2000Tsutsumi et al, , 2003Aoki et al, 2007), Proterozoic zircons are originally derived from the North China Craton and/or the Korean Peninsula. The ages of the basement rocks in the North China Craton have been found to be in the ranges of approximately 2600 -2400 Ma and 2000 -1750 Ma (Zhao et al, 2001).…”
Section: Provenance Of the Clasticsmentioning
confidence: 99%
See 2 more Smart Citations